Sur la place d’Horus dans l’ennéade héliopolitaine - Tillier, Anaïs (Zeitschrift für ägyptische Sprache und Altertumskunde, 2013)
In the study of W. Barta about the ennead of Heliopolis, we note that Horus is often mentioned with the nine gods. This article focuses on various examples of the ennead considering the place of Horus in the enumeration of gods and his specific form. We distinguish three cases: 1) Horus between Isis and Nephthys; 2) Horus between Osiris and Seth (or Isis); 3) Horus after Nephthys, at the end of the ennead. In the first one, Horus replaces Seth, generally during the late period when Seth is banished. In the second case, the order of enumeration follows the one of epagomenal days. In the last one, Horus completes the ennead ( Htm psD.t ) as [R8-V20] “the tenth god”. The noted Horus forms are essentially Harsiesis, Haroeris, Horus of the Great-House ( m Hw.t-aA.t ), Horus of Pe ( m P ) or simply Horus. They are all involved in the osirian myth.